2019
DOI: 10.21018/rjcpr.2019.1.268
|View full text |Cite
|
Sign up to set email alerts
|

Facebook and Public Relations in Higher Education

Abstract: Nowadays It is essential for universities and faculties to interact on-line with their potential applicants, current students as well as other stakeholders. In recent years, social media such as Facebook has provided higher education institutions with new means of communication with their target groups. The purpose of this study is to explore the use of the most popular social network Facebook by selected faculties in the Czech Republic and Slovakia and to provide a set of practical benchmarks on successful co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This then highlights the relevance that Facebook has to modern communication and public relations. Eger, Egerova and Kryston (2019), who suggested that the usage of social media has changed approaches to communication and publication relations by organisations, support this assertion. In the following sections the literature and grounding theory for the study were provided.…”
Section: Facebook Communication and Marketing Influence On Decision-mmentioning
confidence: 99%
See 2 more Smart Citations
“…This then highlights the relevance that Facebook has to modern communication and public relations. Eger, Egerova and Kryston (2019), who suggested that the usage of social media has changed approaches to communication and publication relations by organisations, support this assertion. In the following sections the literature and grounding theory for the study were provided.…”
Section: Facebook Communication and Marketing Influence On Decision-mmentioning
confidence: 99%
“…The main social media platform of interest in this paper was therefore Facebook. Facebook has provided an innovative means of communication to institutions of higher learning (Eger, Egerova & Kryston, 2019). Young adults tend to use Facebook daily for social interactions (Pempek, Yermolayeva & Calvert, 2009).…”
Section: Facebook Communication and Marketing Influence On Decision-mmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is an ample evidence for institutional branding activities that focus on the use of social media in higher education. Furthermore, these activities impact the development of the relationship between an institution and the public and gain students' brand loyalty towards the institution (Eger, Egerova, & Kryston, 2019). Moreover, universities' promotional campaigns can be done transparently on social media and this situation could increase institutional trust thanks to communication activities with users on social media channels (Maresova, Hruska, & Kuca, 2020).…”
Section: Social Media and Higher Education Institutionsmentioning
confidence: 99%
“…Social media have driven content development and sharing between different communities and maintained control over the main trend of the social culture of the digital society [4]. Social media serve as the platform for conducting business, expert branding, and facilitating education [5]. Society is actively exploring the potential of the web and selftraining by means of online courses, marathons, and useful content [6].…”
Section: Introductionmentioning
confidence: 99%